Roman Ingarden's philosophy of literature : phenomenological account - Chojna, Wojciech. (Value Inquiry Book Series, 2017)
In Roman Ingarden's Philosophy of Literature Wojciech Chojna discusses Ingarden's theory of literary works and develops a phenomenological account of identity which accommodates differences in interpretations and value judgments without succumbing to relativism. The latter is overcome not through falling back on essentialism but from within relativism. Literature offers us diverse experiences changing our perceptions of ourselves and the worlds we live inches Absolutism proclaiming unmitigated access to the meaning of literary texts is intolerant of differences and leads to violence in life. Conversely, relativism, in the illusory spirit of radical tolerance, turns meanings and values into historically contingent, incompatible interpretations, where communication and reconciliation is impossible, thus justifying ideological conflicts and violence.